2013
DOI: 10.1093/annonc/mdt016
|View full text |Cite
|
Sign up to set email alerts
|

Dental diagnostic X-ray exposure and risk of benign and malignant brain tumors

Abstract: Background: This study evaluates the risk of benign brain tumors (BBTs) and malignant brain tumors (MBTs) associated with dental diagnostic X-ray, using a large population-based case-control study. Materials and methods:We identified 4123 BBT cases and 16 492 controls without BBT (study 1) and 197 MBT cases and 788 controls without MBT (study 2) from Taiwan National Health Insurance claim data. The risks of both types of tumor were estimated in association with the frequency of received dental diagnostic X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 15 publications
(16 reference statements)
2
18
0
2
Order By: Relevance
“…These studies were the first epidemiological investigations to assess the correlation between dental X-rays and the development of tumors in the brain and parotid glands. Following this, several other groups also examined the effects of dental X-rays on meningioma development (Neuberger et al 1991;Ryan et al 1992;Rodvall et al 1998;Longstreth et al 2004;Claus et al 2012;Lin et al 2013). The results and details of these studies have been summarized in a recent meta-analysis which included seven case-control studies involving 6174 patients and 19,459 controls that reported development of meningioma.…”
Section: Examinationmentioning
confidence: 99%
“…These studies were the first epidemiological investigations to assess the correlation between dental X-rays and the development of tumors in the brain and parotid glands. Following this, several other groups also examined the effects of dental X-rays on meningioma development (Neuberger et al 1991;Ryan et al 1992;Rodvall et al 1998;Longstreth et al 2004;Claus et al 2012;Lin et al 2013). The results and details of these studies have been summarized in a recent meta-analysis which included seven case-control studies involving 6174 patients and 19,459 controls that reported development of meningioma.…”
Section: Examinationmentioning
confidence: 99%
“…La investigación de Lin Mc, que evalúo la asociación entre la presencia de tumores cerebrales y la exposición a radiografía dental, obtuvo que el riesgo para desarrollar tumores cerebrales de tipo benigno aumenta tras aumentar la exposición a rayos X por consulta odontológica; mientras que no hubo asociación significativa con los tumores malignos cerebrales, pero el diseño de este estudio se basó en la selección de casos y controles identificados a partir de las reclamaciones de un millón de personas seleccionadas al azar de la base de datos del Instituto Nacional de Investigación en Salud entre 1996 a 2010, por lo que la veracidad de la información está sujeta al registro oportuno de las reclamaciones (10). Por lo que es necesario tener presente que tras dosis acumuladas es posible contribuir a inducir cambios en la proliferación de tejidos que si bien en sus inicios no tienen potencial de malignidad es posible que, ante otros estímulos, dichos crecimientos tisulares se alteren y puedan derivar en problemas más complejos.…”
Section: Dosis De Rayos X En Odontologíaunclassified
“…Estudios en humanos y animales muestran los daños en salud provocados por la exposición a rayos X en diferentes disciplinas médicas, como ayuda complementaria en el diagnóstico (2)(3)(4)(5)(6)(7)(8)(9)(10)(11); sin embargo, la exposición a radiación en la práctica odontológica, sugiere que, aunque no se requiere de exposiciones a dosis altas ni prolongadas en el tiempo, para los profesionales y estudiantes como para los pacientes las exposiciones pueden ser frecuentes, ya sea por uso no justificado de la radiografía, falta de conocimiento en radiología dental u omisión de consideraciones básicas en radioprotección. Esta situación puede incrementar la dosis recibida, absorbida y la cantidad de radiación acumulada en órganos; sumado a esto, en los pacientes existe la posibilidad de efectos sinérgicos con otras exposiciones a rayos X recibidas durante la atención en otras áreas de salud.…”
Section: Introductionunclassified
“…18 It is a mandatory issue to follow the ALARA principle "As Low as Reasonably Achievable" during dentist routine work. 19 It has been reported in the dental literature that ALARA principles are not strictly applied in the dental field, 20,21 which can be of concern for the dental professional due to the ill effects of radiation.…”
Section: Clinical Relevance Of the Datamentioning
confidence: 99%